ANALISIS PROFIL KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR DI KABUPATEN SUMEDANG - Ai Hayati Rahayu; Poppy Anggraeni (Jurnal Pesona Dasar, 2017)
Science Process Skills (SPS) are all scientific skills used to acquire, develop, and apply scientific concepts and theories. SPS mastery is not only useful in science learning but also for the daily life of the students. Therefore very important mastery of the ability of the process of science since elementary school age.This study aims to obtain an overview of the students' science process skill profile. The research method used is survey method with research subject that is as much as 16 elementary school in Sumedang regency. Data collection techniques used are test techniques. The data have been obtained and then analyzed by simple statistical analysis.Based on the results of research that has been done can be seen that the ability of SPS in elementary school students in Sumedang regency as a whole is still low that has an average value of 9.8, as well as for every aspect of SPS it is still low with a percentage of 49.7%. There is no gender effect on the difference of students' SPS capability because both male and female students have the same low ability of SPS which is 48.7% and 49.1% respectively.